Case report: A novel mutation of glial fibrillary acidic protein gene causing juvenile-onset Alexander disease - Romano, Carmela; Morena, Emanuele; Petrucci, Simona; Diamant, Selene; Marconi, Martina; Travaglini, Lorena; Zanni, Ginevra; Piane, Maria; Salvetti, Marco; Romano, Silvia; Ristori, Giovanni (Frontiers in Neurology, 2024)
Alexander Disease (AxD) is a rare inherited autosomal dominant (AD) disease with different clinical phenotypes according to the age of onset. It is caused by mutations in the Glial Fibrillary Acid Protein (GFAP) gene which causes GFAP accumulation in astrocytes. A wide spectrum of mutations has been described. For some variants, genotype-phenotype correlations have been described, although variable expressivity has been reported in late-onset cases also among members of the same family. We present the case of a 19-year-old female who developed gait ataxia and subtle involuntary movements, preceded by a history of enuresis and severe scoliosis. Her mother was affected by ataxia since her childhood, then complicated by pyramidal signs and heavily worsened through the years. Beyond her mother, no other known relatives suffered from neurologic syndromes. The scenario was further complicated by a complex brain and spinal cord Magnetic Resonance Imaging (MRI) pattern in both mother and daughter. However, the similar clinical phenotype made an inherited cause highly probable. Both AD and autosomal recessive (AR) ataxic syndromes were considered, lacking a part of proband’s pedigree, but not causative genetic alterations were found. Considering the strong suspect for an inherited condition, we performed a clinical exome sequencing (CES), that analyzes more than 4500 genes associated with diseases. CES evidenced the new heterozygous missense variant c.260T>A in exon 1 of glial fibrillary acidic protein (GFAP) gene (NM_002055.4), that causes the valine to aspartate amino acid substitution at codon 87 (p. Val87Asp) in the GFAP. The same heterozygous variant was detected in her mother. This mutation has never been described before in literature. This case should raise awareness for this rare and under-recognized disease in juvenile-adult cases.